Pola Komunikasi Organisasi Karang Taruna Sendang Desa Karanglor, Kecamatan Manyaran, Kabupaten Wonogiri - Widyantoro Yuliatmojo; Anita Tri Utami; Nindita Pramuktisari; Shela Rahmadhani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to examine in depth the organizational structure and communication patterns implemented by Karang Taruna Sendang in Karanglor Village, Manyaran District, over a three-month research period. Using a qualitative descriptive approach, data were gathered from primary sources through direct interviews and observations, as well as secondary sources including organizational documents involving fifteen informants consisting of the chairperson, administrators, and active members. The research subjects were determined using a purposive sampling technique, and data analysis was conducted through an interactive model, while data validity was ensured through triangulation of sources, methods, and time. The findings indicate that Karang Taruna Sendang implements an all-channel (star) communication pattern characterized by open deliberation mechanisms prior to the execution of every activity agenda. This effective communication pattern and smooth information flow have proven capable of minimizing organizational barriers and generating various tangible work programs that provide positive contributions to youth development and the welfare of the community in Karanglor Village.